1984
DOI: 10.1111/j.1360-0443.1984.tb03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking in Longitudinal Perspective: Career and Natural History

Abstract: Longitudinal studies of drinking are now of great importance. Two concepts rued to be distinguished. Career is the evolution ofthe individual's role, while Natural History pertains to the sequential development in tissue or body-system reactivity to alcohol. The richness of ideas and research opportunities relating seperately to each of these dimensions is discussed, and also the need for synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…I also suggested that treatment may well benefit from understanding such ''natural processes of recovery'' (Edwards, 1984).…”
Section: ''Natural Healing Factors''mentioning
confidence: 99%
See 2 more Smart Citations
“…I also suggested that treatment may well benefit from understanding such ''natural processes of recovery'' (Edwards, 1984).…”
Section: ''Natural Healing Factors''mentioning
confidence: 99%
“…In addition, the ongoing work of Moos and his associates (Bromet & Moos, 1977;Finney & Moos, 1992;Moos, Finney, & Chan, 1981) appears to confirm the crucial role of such ''natural'' or ''extratreatment'' factors. It may well be that in order for treatment to be effective, it must be syntonic with such ''natural processes of recovery'' (Edwards, 1984). In order to understand these issues we need research that focuses on dynamics that ''invite and reinforce'' sobriety over the long-term (Taylor, Brown, Duckitt, Edwards, Oppenheimer, & Sheehan, 1985).…”
Section: State Of the Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way in which research findings can actually be fed back to influence clinical care then poses further interesting questions. The Addiction Research Unil has over the years produced work on coping mechanisms and relapse prevention (Litman et a/., 1984), studies on the help seeking process (Thom, 1986(Thom, ,1987, work on the wives of alcoholics (Orford et al, 1975), and research on the special needs of the homeless alcoholic (Edwards et al, 1966), all of which have provided insights which have been integrated into the work of the clinical service Research on the long-term course of alcoholism (Edwards, 1989b) and ideas on 'natural history and career' (Edwards, 1984) have a similar ready follow through to clinical practice. The two-dimensional dependence and problems model to the development of which the ARU's research contributed (Edwards, 1986), provides the clinical worker with a basic framework, and the ARU has developed measures for dependence (SADQ, Stockwell et ai, 1979) and for alcohol related problems (APQ, Drummond, 1990), which are used in the clinical setting.…”
Section: Research As Another Integral Activitymentioning
confidence: 99%
“…Griffith Edwards (1984) was the first to distinguish between the natural history of alcoholism and the career of the drinker. The former implies a process that, if left unchecked by intervention, follows an inevitable progression that is essentially the same for all individuals with the condition.…”
mentioning
confidence: 99%